Origin of fundus hyperautofluorescent spots and their role in retinal degeneration in a mouse model of Goldmann-Favre syndrome - Nan-Kai Wang; Chi-Chun Lai; Chi-Hsiu Liu; Lung-Kun Yeh; Chai Lin Chou; Jian Kong; Takayuki Nagasaki; Stephen H. Tsang; Chung-Liang Chien (The Company of Biologists, 2013)
SUMMARY Goldmann-Favre syndrome, also known as enhanced S-cone syndrome, is an inherited retinal degeneration disease in which a gain of photoreceptor cell types results in retinal dysplasia and degeneration. Although microglia have been implicated in the pathogenesis of many neurodegenerative diseases, the fundamental role of these cells in this disease is unknown. In the current study, sequential analyses suggest that microglia are recruited and appear after outer nuclear layer folding. By crossing rd7 mice (a model for hereditary retinal degeneration owing to Nr2e3 mutation) with mice carrying the macrophage Fas-induced apoptosis (Mafia) transgene, we generated double-mutant mice and studied the role of the resident retinal microglia. Microglial cells in these double-mutant mice express enhanced green fluorescent protein (EGFP) and a suicide gene that can trigger Fas-mediated apoptosis via systemic treatment with AP20187 (FK506 dimerizer). We demonstrated that more than 80% of the EGFP+ cells in retinas from rd7/rd7;Tg/Tg mice express Iba-1 (a microglial marker), and resident microglia are still present in the retina because AP20187 does not cross the blood-brain barrier. Hence, only circulating bone marrow (BM)-derived microglia are depleted. Depletion of circulating BM-derived microglia accelerates retinal degeneration in rd7 mice. An increased number of autofluorescent (AF) spots is a consequence of resident microglia proliferation, which in turn establishes an inflammatory cytokine milieu via the upregulation of IL-1β, IL-6 and TNFα expression. This inflammation is likely to accelerate retinal degeneration. This study not only identifies inflammation as a crucial step in the pathogenesis of retinal degeneration, but also highlights the involvement of specific cytokine genes that could serve as future treatment targets in retinal degenerations.